2017
DOI: 10.1111/andr.12315
|View full text |Cite
|
Sign up to set email alerts
|

Spermatogenesis associated 22 is required for DNA repair and synapsis of homologous chromosomes in mouse germ cells

Abstract: Analysis of the N-ethyl-N-nitrosourea (ENU)-induced repro42 mutation previously identified spermatogenesis associated 22 (Spata22) as a gene required for meiotic progression and fertility in both male and female mice, but its specific contribution to the process was unclear. Here we report on a novel, null allele of Spata22 (Spata22Gt) and confirm its requirement for germ cell development. Similar to repro42 mutant mice, histological and mating analyses indicate that gametogenesis is profoundly affected in Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 45 publications
6
30
0
Order By: Relevance
“…ATRX protein was present in adult human and rat testis and was expressed in spermatogonia, early meiotic spermatocytes and somatic cells [51]. Many members of spermatogenesis associated protein family genes (Sap) are identified in testes and play important roles in the spermatogenesis process in vertebrates including fish, for example, Sap2 [52,53], Sap4 [54], Sap6 [55], Sap22 [56], and so on. In our study, above mentioned genes were also identified to be sex-significant expression genes in testes, which suggest they may paly conserved role in the early spermatogenesis of sturgeon.…”
Section: Discussionmentioning
confidence: 99%
“…ATRX protein was present in adult human and rat testis and was expressed in spermatogonia, early meiotic spermatocytes and somatic cells [51]. Many members of spermatogenesis associated protein family genes (Sap) are identified in testes and play important roles in the spermatogenesis process in vertebrates including fish, for example, Sap2 [52,53], Sap4 [54], Sap6 [55], Sap22 [56], and so on. In our study, above mentioned genes were also identified to be sex-significant expression genes in testes, which suggest they may paly conserved role in the early spermatogenesis of sturgeon.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, the absence of MEIOB induces an arrest at a zygotene/pachytene-like stage with an accumulation of unrepaired DSBs (19,26). Several lines of evidence suggest that during meiosis, MEIOB forms a complex with SPATA22, a meiosis-specific factor with unknown function (26)(27)(28)(29). Moreover, MEIOB and SPATA22 have been shown to interact with and colocalize with RPA subunits; the role and mode of these interactions remain to be understood (19,26,29).…”
Section: Introductionmentioning
confidence: 99%
“…ATRX protein was present in adult human and rat testis and was expressed in spermatogonia, early meiotic spermatocytes and somatic cells [51]. Many members of spermatogenesis associated protein family genes (Sap) are identified in testes and play important roles in the spermatogenesis process in vertebrates including fish, for example, Sap2 [52,53], Sap4 [54], Sap6 [55], Sap22 [56], and so on. In our study, above mentioned genes were also identified to be sex-significant expression genes in testes, which suggest they may paly conserved role in the early spermatogenesis of sturgeon.…”
Section: Discussionmentioning
confidence: 99%